PENGEMBANGAN KURIKULUM MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM PENALARAN DAN PEMECAHAN MASALAH - Yogi Anggraena (Fakultas Tarbiyah Universitas Ibrahimy, 2019)
The Trending topic in International Mathematics and Science Study (TIMSS) and the Program for International Student Assessment (PISA) have become a new standard for mathematics learning. One of the objectives of the study from TIMSS and PISA is to know the students' abilities in reasoning, identifying, and understanding, and using the basic mathematics needed in daily life. Or in other words, students must have mathematical literacy. The concept of mathematical literacy is intended the ability of individuals to formulate, use, and interpret mathematics in various contexts. This includes mathematical reasoning and using mathematical concepts, procedures, facts, and equipment to describe, explain, and predict phenomena or events (OECD, 2013). Indonesia has participated in TIMSS and PISA studies several times, from the TIMSS and PISA study results, it shows that students have not been able to develop optimally about their thinking abilities in mathematics schools and are still low in ability (1) to understand complex information, (2) theory , analysis and problem solving, (3) using tools, procedures and problem solving and (4) conducting investigations. In 2014, the National Council of Teachers of Mathematics (NCTM) stated that learning mathematics today is still too formal, lacks connection with the meaning, understanding, and application of mathematical concepts, and fails to give sufficient attention to the ability of reasoning and solving problem. These results indicate that there needs to be a change in curriculum orientation, which is not to burden students with content but prioritize the aspects of essential abilities needed by all citizens to participate in developing their country in the 21st century. Therefore it is necessary to develop a mathematics curriculum that enhances students' abilities in reasoning and problem solving in order to improve the quality of mathematics for students knowledge and skill in this global era.